Physical and sensory characteristics of hotcakes prepared from mixes with coconut residue flour - Omadto, Benylyn O.
The effects of amounts of coconut residue flour (CRF), antioxidant used and the fat content of CRF on the sensory and physical characteristics of hotcakes prepared from mixes were studied in three phases. Phase I involved the determination of the effects of varying levels of CRF (0,15% & 30%) and antioxidant (BHT and lecithin) on hotcake mix by evaluating the color, flavor, texture and overall acceptability of the cooked hotcakes. In Phase II, the effect of varying levels of fat contents of CRF (23, 28 & 33) in two trials were studied on the sensory attributes and physical characteristics (texture and cell structure) of hotcake with 15% CRF. Phase III dealt with the verification of the results obtained in Phase I and Phase II. Results indicated that 15% CRF is the optimum amount of CRF that can be substituted for wheat flour in hotcake mix with BHT as a better antioxidant. Furthermore, no significant difference was found among samples of hotcake made from mixes 15% CRF of 23, 28 and 33% fat content. The product's cell structure maybe described to be uniform in size, with holes of 0.3-1mm in diameter, but not fairly thin walled.